Legal and policy considerations in the realisation of right to free and compulsory primary education in Kenya (2018)
Intemationally considerations have been given to the need for nations to ensure that there is development in education. Right to education should be promoted and enhanced through the employment of laws and policies. Therefore, the United Nations Declaration on Human Rights (UNDHR), International Covenant on Civil and Political Rights (ICCPR) and International Covenant on Economic, Social and Cultural Rights (ICESCR) and the Convention on the Rights of the Child (CRC) are international best practices that can be invoked to compel the realisation of right to free and compulsory primary education. To realise this from a domestic perspective will require the govemment to consistently fashion out policies and laws for the realisation of free and compulsory primary education. Kenya is one of such countries that have translated these international best practices on the right to free and compulsory primary education through its domestic laws. In particular, the Constitution of Kenya 2010, Basic Education Act and Children’s Act 2001 have set the pace for the realisation of the right. This article seeks assess the policy and legal considerations as motivating factors for supporting the realisation of right to free and compulsory legal education in Kenya